Structural characterization and immunomodulatory effects of extracellular polysaccharide from Lactobacillus paracasei VL8 obtained by gradient ethanol precipitation. Issue 5 (12th April 2022) - Liu, Yuwei; Mao, Kemin; Zhang, Nan; Chitrakar, Bimal; Huang, Pimiao; Wang, Xianghong; Yang,, Bing; Sang, Yaxin
Abstract : Abstract: In this study, gradient ethanol precipitation method was applied to obtain the extracellular polysaccharides of Lactobacillus paracasei VL8 (VL8‐EPS). The yields, physicochemical properties, and immunomodulatory effects of VL8‐EPS obtained by precipitation at different ethanol concentrations (30%, 50%, and 70%, v/v) were compared. The results showed that VL8‐EPSs were high molecular weight sulfated heteropolysaccharides, composed mainly of glucose and galactose, and the alteration of ethanol concentration had an effect on their chemical compositions, molecular weight distributions, monosaccharide composition, and surface structure, while the primary structure remained the same. Among the three polysaccharide fractions, VL8‐EPS50 displayed better immunomodulatory activities compared with VL8‐EPS30 and VL8‐EPS70. VL8‐EPS50 was found to exert immunomodulatory effects by enhancing the phagocytic activity of RAW264.7 cells and to promote their secretion of more nitric oxide; it also showed stronger thermal and solution stability. In summary, there was a correlation between the structural characteristics of polysaccharides and their immunomodulatory activity, and VL8‐EPS50 was preferentially used for in vivo immunomodulatory activity. Practical Application: This study opens up the source of raw materials for functional foods, which can provide some theoretical basis for the research and development of extracellular polysaccharides of lactic acid bacteria and promote their application in the future development of food industry.